Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1017/s1366728916001152
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic structural priming in bilinguals: priming of the subject-to-object raising construction between English and Korean

Abstract: A cross-linguistic structural priming experiment explores the issue of whether parallel syntactic constructions of the two languages in bilinguals share a representation when the surface word orders of the constructions differ. The target population was early balanced bilinguals of Korean and English; the tested constructions were structures relevant to the subject-to-object raising (STOR) operation, which until this study have not been used for structural priming research in cross-linguistic contexts (e.g., S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Syntactic priming has been explored within and between languages (e.g., Bernolet et al, 2013;Kantola & van Gompel, 2011), in aural and written modalities (e.g., Kaan & Chun, 2018;Song & Do, 2018), in comprehension and production (e.g., Hartsuiker et al, 2004;Wei et al, 2017), and in lab-based settings and natural discourse. It has been studied in various languages (e.g., German: Jackson & Ruf, 2017) and with many different methodologies (e.g., confederate scripting tasks, picture description tasks).…”
Section: Syntactic Primingmentioning
confidence: 99%
See 4 more Smart Citations
“…Syntactic priming has been explored within and between languages (e.g., Bernolet et al, 2013;Kantola & van Gompel, 2011), in aural and written modalities (e.g., Kaan & Chun, 2018;Song & Do, 2018), in comprehension and production (e.g., Hartsuiker et al, 2004;Wei et al, 2017), and in lab-based settings and natural discourse. It has been studied in various languages (e.g., German: Jackson & Ruf, 2017) and with many different methodologies (e.g., confederate scripting tasks, picture description tasks).…”
Section: Syntactic Primingmentioning
confidence: 99%
“…In other words, cross-linguistic syntactic priming provides evidence that bilinguals share abstract grammatical representations between two languages. Following Hartsuiker et al (2004), several studies have evaluated the shared-syntax account using different methodologies, priming directions (i.e., L1 -L2, L2 -L1), and constructions (Bernolet et al, 2007(Bernolet et al, , 2009(Bernolet et al, , 2012(Bernolet et al, , 2013Cai et al, 2011;Chen et al, 2013;Hartsuiker et al, 2016;Hartsuiker et al, 2004;Kantola & van Gompel, 2011;Loebell & Bock, 2003;Salamoura & Williams, 2007;Shin & Christianson, 2009;Song & Do, 2018;Weber & Indefrey, 2009). For instance, Kantola and van Gompel (2011) found that Swedish L2 English learners showed equally strong syntactic priming effects when they completed Swedish or English sentence fragments after they were exposed to an English or Swedish prime sentence, where both the fragments and the prime sentences employed either a ditransitive or prepositional dative construction.…”
Section: Syntactic Primingmentioning
confidence: 99%
See 3 more Smart Citations